Properties of the System for the Mixed Function Oxidation of Kaurene and Kaurene Derivatives in Microsomes of the Immature Seed of Marah macrocarpus: Electron Transfer Components - Hasson, Edna P. (1976)
Cytochrome P-450 and cytochrome b(5) at levels of approximately 0.10 and 0.60 nanomole per milligram of microsomal protein were detected by spectral measurements in microsomes prepared from endosperm tissue of immature Marah macrocarpus seeds. TPNH-cytochrome c reductase, DPNH-cytochrome c reductase, andDPNH-cytochrome b(5) reductase activities were also present in these microsomes at levels of approximately 0.060, 0.22, and 0.52 unit per milligram of microsomal protein, respectively. (One unit of reductase is the amount of enzyme catalyzing the reduction of 1 micromole of electron acceptor per minute.) Treatments of microsomes with steapsin or trypsin were not effective in solubilizing any of these electron transport components in detectable form. However, treatment of a microsomal suspension in 25% glycerol with 1% sodium deoxycholate led to the release of about 60% of the protein and each of the above hemoproteins and electron transfer activities to the fraction which was not pelleted after centrifugation for 2 hours at 105,000g. Some ent-kaur-16-ene oxidase activity could be detected in the solubilized fraction after removal of the detergent. Cytochrome b(5) and DPNH-cytochrome b(5) reductase activity were largely separated from one another and from an overlapping mixture of TPNH-cytochrome c reductase and DPNH-cytochrome c reductase when the sodium deoxycholate-solubilized fraction was chromatographed on a DEAE-cellulose column. No cytochrome P-450 or cytochrome P-420 was detected in the column fractions and no ent-kaur-16-ene oxidase activity was detected when the column fractions were tested singly or in combination. The possible participation of these components in the mixed function oxidation of ent-kaur-16-ene and a number of its oxidized derivatives catalyzed by these microsomes is discussed in relation to the model which has been developed to explain the function of analogous components in mixed function oxidase reactions in mammalian liver microsomes.